Treatment of nitrogen micro-polluted wastewater using a new type of biological folded non-aerated filter (BFNAF): Performance, microbial community and machine learning optimization - Jie Han; Youzhao Wang; Mingdong Chang; Xiaoyan Dang; Shumin He; Xiaodi Huang; Yongguang Ma; Zhipeng Wang; Yaonan Zhu; Junnan Liu; Jinxiang Wang; Lin Zhai; et al. (Journal of Environmental Chemical Engineering, 2026)

Anemoside B4 upregulates DDAH2 and attenuates oxidative stress induced endothelial dysfunction - Shuxian Lu; Yao Yi; Qin Chen; Luling He; Margaret Baldini; Dan Shan; Limin Gong; Liang Qiu; Shumin Ma; Manman Qin; Yanyun Fang; Yifeng Zhang; et al. (Molecular and Cellular Biochemistry, 2026)

Threshold responses of diatom community to hydrological changes in an alpine peatland based on long-term (2014–2020) monitoring data - Xu Chen; Junlu Li; Jia Peng; Shuangyu Xu; Jun He; Shumin Qiao; Linghan Zeng; Xianyu Huang (Journal of Hydrology, 2026)

Sensitive detection of PFOA in environmental water based on Pt/MnO2 nanozymes with engineered d-band structure - Haiyang Wang; Di Wu; Cuiyu Huang; Shumin Wang; Xiwen He; Langxing Chen; Yukui Zhang (Journal of Hazardous Materials, 2026)

Impacts of processing and environmental factors on fucoxanthin from brown algae: structural stability, bioactivity, and underlying molecular mechanisms - Shumin Cai; Mingrui Ma; Jialin Li; Yingying Zhao; Yimeng Ren; Dandan Ren; Yunhai He; Yidi Cai; Shu Liu; Qiukuan Wang; Yichao Ma (Food Chemistry, 2026)

Effects of Antioxidant DI-3-N-Butylphthalide on Hemorrhagic Transformation Assessed by Propensity Score Matching in a Real-World Thrombolyzed Ischemic Stroke Patient Setting - Ziqi Han; He Liang; Tieping Fan; Mario Minor Murakami Junior; Shumin Li; Ruikang Sun; Daoyong Peng; Shiwei Du; Yu Hasegawa; Haojie Gao; Dong Chen; Dirk M. Hermann; et al. (Translational Stroke Research, 2026)

Phytochemicals from the leaves of Staphylea arguta (Turpiniae Folium) and their anti-inflammatory activity - Shumin Wu; Feifei Tang; Xiyu Xu; Xiaoxiang Fan; Danting Luo; Yunqing He; Ping Hai; Shengxiang Yang; Yuan Gao; Jian Yang (Natural Product Research, 2026)

Fine-mapping and candidate gene analysis of qFF3.1 conferring fruit firmness in a modern tomato variety - Yunhao Han; Xin Li; Can Zhu; Yonglian Wang; Junling Hu; Shumin He; Saifeng Guo; Xiaoxiao Lu; Chunyang Pan; Zejun Huang; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2026)

Thermoresponsive gamma-cyclodextrin-based porous composite functionalized with N-isopropylacrylamide and soybean hull polysaccharide for controlled curcumin delivery - Shumin Wang; Shengnan Wang; Ziyang Zhang; Jun Li; He Liu; Chunlei Liu (Journal of Food Engineering, 2026)

Voltage-regulation bioelectrochemical sulfur autotrophic denitrification (BESAD) with sulfur-based cathodes: Enhanced nitrogen removal and mechanism - Xiaoyan Dang; Youzhao Wang; Chaoyue Zhao; Xiubo Chen; Yaonan Zhu; Xiaolong Gao; Kuo Zhang; Shumin He; Jie Han; Jiedong Hao; Tong Zhu (Journal of Environmental Chemical Engineering, 2026)

Synergistic KOH/MgSO₄ activation of hazelnut shell biochar: Tailored hierarchical porosity and surface chemistry boosting high-efficiency capacitive deionization - Shumin He; Youzhao Wang; Xiaolong Gao; Jiedong Hao; Enbo Zhang; Rui Du; Tengfei Li; Yaonan Zhu; Tong Zhu (Journal of Environmental Chemical Engineering, 2025)

Bile acids and apical sodium-dependent bile acid transporter impact per- and polyfluoroalkyl substances absorption: Evidence from in vivo and cross-sectional studies - Yiran Liang; Jing Zhan; Xiao Liu; Shumin Liang; Ruosi Li; Yinchuan Lv; Jingjing He; Jiaying Liu (Journal of Hazardous Materials, 2025)

Macrophage cytoskeletal and immune responses to photoaged and gastrointestinal-transformed polylactic acid micro/nanoplastics with protein corona - Xuri Wu; Feng Tan; Han Zhang; Liping Huang; Yan Wang; Xin He; Rui Cai; Shumin Li (Journal of Hazardous Materials, 2025)

Glutathione responsive curcumin delivery via amino acid covalently grafted cyclodextrin metal organic framework coated with soy hull polysaccharides - Shumin Wang; Shengnan Wang; Xiuzhi Cao; Lina Yang; He Liu (Food Chemistry, 2025)

Biomimetic nanozyme outperforms natural counterpart: Unlocking novel CO2 sequestration potential - Shumin Ni; Weifeng Lyu; Zemin Ji; Lu Wang; Mingyuan Wang; Chang He; Kai Wang; Yue Guan; Keqiang Wei; Xiuxiu Pan (Journal of Cleaner Production, 2025)

Constructing and characterization of cyclodextrin metal organic framework and soybean hull polysaccharide polymer composite carriers: Enhancing curcumin delivery - Shumin Wang; Shengnan Wang; Lanxin Zhang; Peng Wang; He Liu (Food Chemistry, 2025)

Interdecadal variability and possible drivers of summer extreme precipitation on the low latitude plateau of southwestern China - Yan Jin; Yunxia Wan; Huahong Li; Chaoyong Tu; Hongming Yan; Yunsha Hai; Huigeng He; Shumin Chen; Min Xie (Theoretical and Applied Climatology, 2025)

Identification of microbiological genomes carrying antibiotic resistance genes and virulence factor genes for microbiological risk assessment in filter backwash water - Yongjie Huang; Xiaoyao Weng; Xinlu Qu; Tianxiao Sun; Weiwei Zhang; Shumin Yang; Xin He; Yuan Xiao; Tianyang Zhang; Yulin Tang (Journal of Environmental Chemical Engineering, 2024)

Enhancing Lactobacillus plantarum delivery: Impact of gluconolactone concentration on high-internal-phase emulsion gels and gastrointestinal viability - Chenyuan Sun; Shengnan Wang; Yan Xu; Shumin Wang; Dayu Zhou; He Liu (Food Chemistry, 2024)

Thermal aggregation behavior of silver carp myofibrillar protein at low salt content: Effect of oat β-glucan combined with ultrasound-assisted heating - Honglei Zhao; Xueli He; Yanan Lv; Yongxia Xu; Shumin Yi; Jianrong Li; Xuepeng Li (Food Chemistry, 2024)

pH-responsive Aminated mesoporous silica microspheres modified with soybean hull polysaccharides for curcumin encapsulation and controlled release - Shumin Wang; Shengnan Wang; Lina Yang; Peng Wang; Hong Song; He Liu (Food Chemistry, 2024)

Use of modified poly-epoxysuccinic acid as an efficient scale inhibitor to control CaSO4 scaling in NF processes: Performance and mechanisms - Xinyuan Yi; Shumin Yang; Xin He; Zhiwei Wang; Min Rui; Yulin Tang (Desalination, 2024)

Development and characterization of adhesives constructed by soy protein isolate and tea polyphenols for enhanced tensile strength in plant-protein meat applications - Zixi Xue; Minghao Zhang; Meiquan Wang; Shengnan Wang; Shumin Wang; Peng Wang; Jun Li; He Liu (Food Chemistry, 2024)

Occurrence, distribution characteristics and exposure assessment of perchlorate in the environment in China - Diancheng Dou; Ming He; Jinxin Liu; Shumin Xiao; Fu Gao; Wei An; Li Qi (Journal of Hazardous Materials, 2024)

Characterization of high-internal-phase emulsions based on soy protein isolate with varying concentrations of soy hull polysaccharide and their capabilities for probiotic delivery: In vivo and in vitro release and thermal stability - Chenyuan Sun; Shengnan Wang; Shumin Wang; Peng Wang; Guangchen Zhang; He Liu; Danshi Zhu (Food Research International, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

Potential mitigation of titanium dioxide nanoparticles against 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis through inhibiting the canonical NF-κB pathway - Yanjun Gao; Langzhi He; Shumin Duan; Hasen Bilige; Lizhi Lyu; Zihui Li; Hongbo Wang; Chen Li; Yun Wang (NanoImpact, 2024)

Photodegradation of oxytetracycline hydrochloride by Z-scheme g-C3N4 @MIL-101(Fe) heterojunction: Experimental optimization, mechanism evaluation and practical application - Hongbin He; Bolong Liang; Shumin Lin; Yan Chen; Xin Zhang; Shu-Xuan Liang (Journal of Environmental Chemical Engineering, 2024)

Structural, physicochemical, prebiotic properties of guava pulp insoluble dietary fiber and its quality enhancement ability on cow/goat yogurt: Impacts of ultrasound-assisted enzyme treatment - Jingyi Wang; Shumin He; Sihong Tao; Shuzhen Ma; Yufan Luo; Muci Wu; Mengzhou Zhou (Food Bioscience, 2024)

Application of Multi-Strategy Based Improved DBO Algorithm in Optimal Scheduling of Reservoir Groups - Ji He; Wen Guo; Songlin Wang; Haitao Chen; Xiaoqi Guo; Shumin Li (Water Resources Management, 2024)

Using machine learning to trace the pollution sources of disinfection by-products precursors compared to receptor models - Yuan Xiao; Shunjun Ma; Shumin Yang; Huan He; Xin He; Cheng Li; Yuheng Feng; Bin Xu; Yulin Tang (Science of The Total Environment, 2024)

In Vitro Virulence Contrast of Seven Genetically Distinct Toxoplasma gondii Isolates After Rejuvenation In Vivo - Haiting Guo; Jie Tan; Yulin He; Shumin Yuan; Ke Jin; Zhongyuan Li (Acta Parasitologica, 2024)

Storage stability and interfacial rheology analysis of high-internal-phase emulsions stabilized by soy hull polysaccharide - Hui Yang; Shengnan Wang; Yan Xu; Shumin Wang; Lina Yang; Hong Song; Yutang He; He Liu (Food Chemistry, 2023)

Diversity, community structure, and quantity of eukaryotic phytoplankton revealed using 18S rRNA and plastid 16S rRNA genes and pigment markers: a case study of the Pearl River Estuary - Shumin Xu; Guihao Li; Cui He; Yi Huang; Dan Yu; Huiwen Deng; Zhuyin Tong; Yichong Wang; Christine Dupuy; Bangqin Huang; Zhuo Shen; Jie Xu; et al. (Marine Life Science & Technology, 2023)
Understanding consistencies and discrepancies in characterizing diversity and quantity of phytoplankton is essential for better modeling ecosystem change. In this study, eukaryotic phytoplankton in the Pearl River Estuary, South China Sea were investigated using nuclear 18S rRNA and plastid 16S or 23S rRNA genes and pigment analysis. It was found that 18S abundance poorly explained the variations in total chlorophyll a (Chl- a ). However, the ratios of log-transformed 18S abundance to Chl- a in the major phytoplankton groups were generally environment dependent, suggesting that the ratio has potential as an indicator of the physiological state of phytoplankton. The richness of 18S-based operational taxonomic units was positively correlated with the richness of 16S-based amplicon sequence variants of the whole phytoplankton community, but insignificant or weak for individual phytoplankton groups. Overall, the 18S based, rather than the 16S based, community structure had a greater similarity to pigment-based estimations. Relative to the pigment data, the proportion of haptophytes in the 18S dataset, and diatoms and cryptophytes in the 16S dataset, were underestimated. This study highlights that 18S metabarcoding tends to reflect biomass-based community organization of eukaryotic phytoplankton. Because there were lower copy numbers of plastid 16S than 18S per genome, metabarcoding of 16S probably approximates cell abundance-based community organization. Changes in biomass organization of the pigment-based community were sensitive to environmental changes. Taken together, multiple methodologies are recommended to be applied to more accurately profile the diversity and community composition of phytoplankton in natural ecosystems.

Electrochemical oxidation of chloramphenicol by modified Sm-PEG-PbO2 anodes: Performance and mechanism - Chaoyang Zhang; Conghao Gao; Shumin Yang; Xin He; Yue Chen; Xiao Qin; Yulin Tang (Chemosphere, 2023)

Ursolic acid promotes microglial polarization toward the M2 phenotype via PPARγ regulation of MMP2 transcription - Yuye Wang; Luying Qiu; Shumin Deng; Fang Liu; Zhiyi He; Mengye Li; Yanzhe Wang (NeuroToxicology, 2023)

Novel Insight into Glial Biology and Diseases - Cheng He; Shumin Duan (Neuroscience Bulletin, 2023)

P62/SQSTM1 upregulates NQO1 transcription via Nrf2/Keap1a signaling pathway to resist microcystins-induced oxidative stress in freshwater mussel Cristaria plicata - Jielian Wu; Shumin Hou; Lang Yang; Yanrui Wang; Chungen Wen; Yuping Guo; Shanshan Luo; Haihong Fang; He Jiao; Hui Xu; Shuangping Zhang (Aquatic Toxicology, 2023)

Migration and diffusion of unsteady-state flow of volatile organic compounds on activated carbon adsorption beds under reverse ventilation - Tao Liu; Ning Qiang; Jiao He; Haichao Miao; Zhaohai Li; Yiqi Cao; Tianzhe Shi; Shumin Chen (Chemosphere, 2023)

Depth and Heading Control of a Manta Robot Based on S-Plane Control - Yue He; Yu Xie; Guang Pan; Yonghui Cao; Qiaogao Huang; Shumin Ma; Daili Zhang; Yong Cao (Journal of Marine Science and Engineering, 2022)
Bionic underwater robots have many advantages such as high mobility, high efficiency, high affinity, etc. They are especially suitable for tasks such as collecting hydrographic information and for detailed surveys of the marine environment. These tasks are based on their high-precision attitude control. Therefore, this paper proposes a control scheme for a bionic underwater robot—a manta robot. To improve the depth retention capability of the manta robot, a S-plane controller based on asymmetric output was designed in combination with the longitudinal motion characteristics of the manta robot. In addition, to achieve good motion control for the manta robot under conditions of large changes in the heading angle, the fuzzy controller and the heading transition target value function were combined to design the heading controller of the manta robot. Finally, the feasibility and reliability of the control system of the manta robot were verified by pool experiments. The experimental results showed that the depth control error was within ±5 cm and the heading control error was within ±5 degrees. The control scheme proposed in this paper achieves high-precision attitude control of the manta robot, providing a basis for the practical application of the manta robot.

Alleviating the Influence of Circadian Rhythms and Drug Properties to the Release of Paliperidone Gel Matrix Tablets with Compression Coating Technology and Microenvironment Shaping - Zherui Zhang; Shumin Chen; Man Wen; Haibing He; Yu Zhang; Tian Yin; Jingxin Gou; Xing Tang (AAPS PharmSciTech, 2022)

Preliminary study on relationships among nutritional risk, serum prealbumin, and peripheral blood T cell subsets in patients with severe COVID-19 - Yanli Li; Yanbo Sun; Jing He; Peng Zhao; Pengju Luo; Jinsong Bai; Weiming Li; Shumin Li; Yueying Lin; Yunyun Cen (Infectious Diseases, 2021)

Spatial econometric analysis of carbon emission intensity in Chinese provinces from the perspective of innovation-driven - Song Liang; Jingfeng Zhao; Shumin He; Qingqing Xu; Xin Ma (Environmental Science and Pollution Research, 2019)

Adsorption performance and mechanisms of Pb(II), Cd(II), and Mn(II) removal by a β-cyclodextrin derivative - Mengjiao Zhang; Liyun Zhu; Changhua He; Xiaojun Xu; Zhengyang Duan; Shuli Liu; Mingyao Song; Shumin Song; Jiemei Shi; Yu’e Li; Guangzhu Cao (Environmental Science and Pollution Research, 2019)

Spy1 participates in the proliferation and apoptosis of epithelial ovarian cancer - Shumin Lu; Rong Liu; Min Su; Yingze Wei; Shuyun Yang; Song He; Xia Wang; Fulin Qiang; Chen Chen; Shuyang Zhao; Weiwei Zhang; Pan Xu; et al. (Journal of Molecular Histology, 2016)

Antimicrobial effect and membrane-active mechanism of tea polyphenols against Serratia marcescens - Shumin Yi; Wei Wang; Fengling Bai; Junli Zhu; Jianrong Li; Xuepeng Li; Yongxia Xu; Tong Sun; Yutang He (World Journal of Microbiology and Biotechnology, 2014)

Methylated promoters of genes encoding protocadherins as a new cancer biomarker family - Xinbing Sui; Da Wang; Shumin Geng; Gongli Zhou; Chao He; Xiaotong Hu (Molecular Biology Reports, 2012)

Association of adiponectin gene polymorphisms with the risk of ischemic stroke in a Chinese Han population - Fang Liu; Zhiyi He; Shumin Deng; Hui Zhang; Nan Li; Jialiang Xu (Molecular Biology Reports, 2011)

Association of Apolipoprotein M Gene Polymorphisms with Ischemic Stroke in a Han Chinese Population - Dongxue Zhao; Zhiyi He; Xue Qin; Lei Li; Fang Liu; Shumin Deng (Journal of Molecular Neuroscience, 2011)